2013
DOI: 10.1159/000353133
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of K-<b><i>ras</i></b> Codon 12 Mutation in Patients with Resected Gallbladder Cancer

Abstract: Background: Point mutation of K-ras is associated with carcinogenesis and overall survival in various cancers. We investigated the mutational spectrum of K-ras codon 12 in resected normal and gallbladder cancer tissue samples in a Northern Indian population and correlated it with different clinicopathological parameters. Patients and Methods: Gallbladder tissues from normal (n = 24) and cancer patients (n = 39) were analyzed for K-ras codon 12 mutation by restriction fragment length polymorphism. Statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
(26 reference statements)
0
14
0
2
Order By: Relevance
“…Decrease in CCK receptors may be involved in the pathogenesis of gallstone formation resulting in decreased gallbladder motility. It has been observed that gallstones are present in nearly 80% of patients with GBC [11, 12]. Moreover, abnormal processing of CCKAR is found to be associated with gallstones and obesity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Decrease in CCK receptors may be involved in the pathogenesis of gallstone formation resulting in decreased gallbladder motility. It has been observed that gallstones are present in nearly 80% of patients with GBC [11, 12]. Moreover, abnormal processing of CCKAR is found to be associated with gallstones and obesity [13].…”
Section: Introductionmentioning
confidence: 99%
“…This mutation plays an important role in the early stage of carcinogenesis of biliary mucosa, especially in association with AUPBD (Sagawa et al, 1998). Therefore, the frequency of K-ras mutation has widely been reported to be 0% to 41% in gallbladder cancer patients according to the presence or absence of the AUPBD (Kim et al, 2001;Deshpande et al, 2011;Kazmi et al, 2013). A significant difference in the frequency of this mutation has been reported between gallbladder cancer patients with and without AUPBD in a previous study (Hanada et al, 1999).…”
Section: K-ras Genementioning
confidence: 95%
“…It is converted to an active oncogene through point mutations concentrated in codons 12, 13, and 61 by some carcinogens (Stolze et al, 2015). The frequency of K-ras mutations in gallbladder cancer patients was reported to be 0% to 41% (Kim et al, 2001;Deshpande et al, 2011;Kazmi et al, 2013). However, to our knowledge, data on the associations between these mutations and gallbladder cancer in Peru are limited.…”
Section: Introductionmentioning
confidence: 97%
“…Gallbladder cancer (GBC) is the most common malignancy of biliary tract with marked ethnic and geographical variations including Northern Indian gangetic belt (Pandey et al, 2001;Misra et al, 2003;Gupta et al, 2012;Kazmi et al, 2013). Poor prognosis due to late diagnosis and early dissemination is the common characteristic of this dreaded disease (Dhir and Mohandas, 1999).…”
Section: Introductionmentioning
confidence: 99%